Association Between Changes in Oral Health-Related Quality of Life and Depressive Symptoms in the Korean Elderly Population - Kyoung Eun Park; Hooyeon Lee; Young Dae Kwon; Sukil Kim (Frontiers Media S.A., 2023)
Objectives: The aim of this study was to examine the association between changes in oral health related quality of life (OHRQoL) and depressive symptoms in the elderly South Koreans.Methods: We used the 2018 and 2020 Korean Longitudinal Study of Ageing data. Our study population was a total of 3,604 participants aged over 65 in 2018. The independent variable of interest was the changes in the Geriatric Oral Health Assessment Index as OHRQoL between 2018 and 2020. The dependent variable was depressive symptoms in 2020. Multivariable logistic regression analyzed the associations between changes in OHRQoL and depressive symptoms.Results: Participants with improvement in OHRQoL over 2-year period were likely to have fewer depressive symptoms in 2020. Especially, changes in the oral pain and discomfort dimension score was associated with depressive symptoms. A decline in oral physical function, such as difficulty in chewing and speaking, was also associated with depressive symptoms.Conclusion: Negative change in OHRQoL is a risk factor for depression in elderly. This results suggest the importance of maintaining good oral health in later life, as a protective factor against depression.